PENDAMPINGAN BELAJAR MEMBACA AL-QUR’AN MENGGUNAKAN METODE IQRA’ PADA USIA LANJUT DI DUKUH CEMETUK DESA LOROG KECAMATAN TAWANGSARI KABUPATEN SUKOHARJO - P Praptiningsih; Muhammad Nur Ainunajip; Ina Sopiana; Annafora Shafa Mayovabella Nugraha; Alfi Yuliastuti; Zunisa Nur Aini; Shoffin Arfian (AL HAZIQ: Journal of Community Service, 2025)
This community service program aims to assist elderly individuals in reading the Qur’an using the Iqra’ method in Dukuh Cemetuk, Lorog Village, Tawangsari District, Sukoharjo Regency. The initiative stems from the observation that many elderly people are still unable to read the Qur’an fluently, despite having a strong motivation to learn. The approach used is individual participatory learning, guided by andragogical strategies that accommodate the characteristics of older learners. Adult education is understood as a voluntary effort directed toward personal development, independent of any formal obligation. The program was implemented through small halaqah study groups, covering materials such as the introduction to Hijaiyah letters, basic tajweed, and exercises in reading and memorizing short surahs. The results indicate a progressive improvement in Iqra’ reading skills and a heightened religious enthusiasm among participants. This activity confirms that appropriate instructional approaches for the elderly can significantly enhance their Qur’anic reading skills and spiritual well-being.